POS Tagging of Sindhi Language Using Subword Representations and Neural Models - Jagroop Kaur (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Part-of-Speech (POS) tagging is a fundamental Natural Language Processing (NLP) task that facilitates a wide range of downstream applications. While extensive research exists for resource-rich languages such as English and Chinese, morphologically rich and low-resource languages like Sindhi remain underexplored. This paper presents POS tagging models for Sindhi using word-level, character-level, joint word-character, and subword-level representations. To address challenges such as ambiguity, semantic preservation, and out-of-vocabulary (OOV) words, we employ Byte Pair Encoding (BPE) based subword representations in combination with Bidirectional Long Short-Term Memory (BiLSTM) networks. Two classifier settings are evaluated: a Dense layer and a Conditional Random Field (CRF) layer. Experiments are conducted on publicly available Sindhi datasets (SiPOS and Dootio-Wagan), with Dataset-1 used for training and Dataset-2 for evaluation. Results show that joint word-character BiLSTM-CRF achieves the highest accuracy (90%), while the proposed BPE-based subword BiLSTM-Dense model achieves 88%, outperforming the subword BiLSTM-CRF at 86%. These findings demonstrate that subword representations effectively handle OOV and morphological complexity while retaining semantic information. The proposed models enrich Sindhi computational resources and highlight promising directions for future work, including training Sindhi-specific BPE embeddings and exploring transformer-based architectures such as RoBERTa and GPT-2 for improved accuracy.